Peran Filsafat Ilmu dalam Mengembangkan Nalar Ilmiah Mahasiswa Pascasarjana Pendidikan IPS Universitas Negeri Makassar - Prahastini, Sinta; Wulandari, Astria; Syukur, Muhammad; Ahmad, Muhammad Ridwan Said (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The digital era has brought significant changes in the way students access, process, and evaluate information, thereby demanding more advanced scientific reasoning skills. This study aims to analyze the role of the philosophy of science in developing the scientific reasoning of graduate students in Social Studies Education at Makassar State University amidst the challenges of the digital era, characterized by information overload, misinformation, and algorithmic bias. This study uses a descriptive qualitative approach, with data obtained through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model with stages of data reduction, data presentation, and drawing conclusions. The research results show that students have a high understanding of the philosophy of science, covering the aspects of ontology, epistemology, and axiology, and are able to apply it in academic activities. The findings also indicate that students' critical thinking skills are in the high category, although the aspects of evaluation and inference still need strengthening. This study confirms that a deep understanding of the philosophy of science contributes significantly to shaping a critical, systematic, and reflective mindset, thus serving as an important foundation in facing the complexity of information in the digital era. Therefore, integrating the philosophy of science into higher education becomes a strategic step in building an academic generation that is adaptive, ethical, and possesses strong reasoning abilities.